ii.) derive the statements using inference rules and logical equivalences for propositional logic.

i.(R->S)^Q

ii. (J^Q)->P

iii. Q->Z

iv.P-> -Q (v) (R->S)->(-H->J)

Code:derive Z: Q->Z =Z ? derive: -P 1. (J^Q)->P 2. P-> -Q (v) (R->S)->(-H->J) 3. ? c.) derive -(j^Q) 1. maybe (J^Q)->P 2. P-> -Q 3.? d.)derive -J 1.P-> -Q (v) (R->S)->(-H->J) 2.-H->J == -J->H 3.not sure about this one. e.) derive H 1..P-> -Q (v) (R->S)->(-H->J) I'm not sure how to prove it with this one. Can you please help with this.